Accelerated chondrogenic differentiation of stem cells by SOX9 mRNA/dexamethasone-co-loaded lipid nanoparticle for efficient cartilage repair - Ji Sun Park; Hayoung Jeon; Yeeun Lee; Seong Gi Lim; Seo Young Cheon; In-Beom Kim; Hongsoo Choi; Heebeom Koo (Chemical Engineering Journal, 2026)

Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Comparison of the Growth and Internal Quality of Red Radish (Raphanus sativus L. cv. Cherry One) Cultivated Under Different Hydroponic Systems and LED Light Qualities - Ah Young Shin; Joo Hwan Lee; Yong Beom Kwon; Yu Jin Kang; In-Lee Choi; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2026)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Effects of exogenous L-glutamic acid and supplemental LED lighting on the growth and yield of Paprika - Yong Beom Kwon; Joo Hwan Lee; Min Ji Kim; Da Young Lee; In-Lee Choi; Hyuk Sung Yoon; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2025)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Ashish Sharma; Hanjae Kim; Gunhee Kim; Jinhyeon Kang; Cheong Beom Lee; Sung Yong Bae; Hochan Song; Kyeounghak Kim; Jong Hyun Kim; In Hwan Jung; Dong-Won Kang; Jihoon Lee; et al. (Chemical Engineering Journal, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Impact of road embankment construction on groundwater system in alluvial aquifers - Dahye Kim; Beom Geun Cha; In Wook Yeo (Geosciences Journal, 2023)

Worldwide patent trend analysis of herbicide-resistant genes - Beom Yong Kim; In-Jung Kim (Plant Biotechnology Reports, 2022)

Effect of different planting times on the quantitative variation of total seed isoflavone content and composition in Korean soybean cultivars (Glycine max (L.) Merr.) - Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Tae-Joung Ha; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
There is great interest in the enhancement of isoflavones as one of the functional ingredients in soybean. This study aimed to investigate the effects of changes in the ecological environment over different planting times on isoflavone content. A total of 28 Korean soybean cultivars were grown at different planting times in late May, mid-June, and early July and their isoflavone content was measured over 2 years (2017 and 2018). Analyses of variance revealed significant effects of genotypes, planting times, years, and their interactions on isoflavone content. The average content of total isoflavone, as well as its component groups of malonylglucoside and aglycon, increased significantly as the seed planting time was delayed from late May to early July. The accumulation of each isoflavone component varied with changes in the planting time. The isoflavone content of the soybean cultivars for soy-sprout and soy-paste and tofu were higher for plantings in early July than for those in late May and/or mid-June, except for the black soybean cultivars. Despite significant correlations of the isoflavone content of the 28 cultivars among the three planting times, the responses of individual cultivars varied in isoflavone content by planting time. When planting was delayed, the time to flowering and maturity was also delayed and the number of days of growth from planting or flowering to maturity decreased; however, this was not related to isoflavone content. When planting was delayed, the temperature during the ripening period from flowering to maturity was lower, which was inversely related to the isoflavone content.

Analysis of differentially expressed genes in soybean leaf tissue of tolerant and susceptible cultivars under flooding stress revealed by RNA sequencing - Sanjeev K. Dhungana; Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
Flooding stress causes severe yield reduction in soybean worldwide. The development of stress-tolerant cultivars could be an effective measure to reduce the negative effects of flooding stress. Molecular information on the gene expression pattern of tolerant and susceptible genotypes under flooding stress could be valuable to improve the flooding tolerance in soybean. The objective of this study was to analyze the differentially expressed genes (DEGs) revealed by RNA sequencing in the soybean leaf tissues of tolerant (‘Paldalkong’ and ‘Danbaekkong’) and susceptible (‘NTS1116’) cultivars under flooding stress. Seedlings were grown in a well-watered condition up to the V1–V2 stage and flood-stressed by inundating ~ 10-cm water for 14 days. A total of 22,468 genes were differentially expressed in flood-stressed condition compared to the well-watered control condition, out of which 13,729, 13,405, and 13,160 were differentially expressed in ‘Paldalkong’, ‘Danbaekkong’, and ‘NTS1116’, respectively. A higher number of some of the flooding tolerance-related genes such as lipoxygenase, expansin, glutathione S-transferase, and sugar efflux transporter were up-regulated in the tolerant cultivars than in the susceptible cultivar. The number of some abscisic acid-related transcription factors of basic leucine zipper domain and myeloblastosis families was also higher in the tolerant cultivars than in the susceptible cultivar. The molecular information about the DEGs of tolerant and susceptible cultivars obtained in the present study could be valuable to improve the flooding tolerance in soybeans.

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

Role of T-type Calcium Channels in Generating Hyperexcitatory Behaviors during Emergence from Sevoflurane Anesthesia in Neonatal Rats - Feng-Yan Shen; Byung-Gun Lim; Wen Wen; Yu Zhang; Bo Cao; Yue-Guang Si; Li-Qing Ma; Meng Deng; Yang In Kim; Young-Beom Kim; Ying-Wei Wang (Neuroscience Bulletin, 2020)

Implantable electrical stimulation bioreactor with liquid crystal polymer-based electrodes for enhanced bone regeneration at mandibular large defects in rabbit - Chaebin Kim; Hoon Joo Yang; Tae Hyung Cho; Beom Seok Lee; Tae Mok Gwon; Soowon Shin; In Sook Kim; Sung June Kim; Soon Jung Hwang (Medical & Biological Engineering & Computing, 2020)

Trpm2 Ablation Accelerates Protein Aggregation by Impaired ADPR and Autophagic Clearance in the Brain - Yongwoo Jang; Byeongjun Lee; Hyungsup Kim; Seungmoon Jung; Sung Hoon Lee; So-Young Lee; Ji Hyun Jeon; In-Beom Kim; Seo-Ho Lee; Byung-Ju Kim; Uh-Hyun Kim; Yunjong Lee; et al. (Molecular Neurobiology, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Chloroform induces cystein-rich 61, a mediator of collagen homeostasis via early growth response-1 dependent pathway in human skin dermal fibroblasts - Hana Lee; Jae Beom Park; Woo-In Ryu; Ji Hyun Kim; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Ectopic expression of a hot pepper bZIP-like transcription factor in potato enhances drought tolerance without decreasing tuber yield - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; In Sun Yoon; Dongjin Shin; Myung-Ok Byun; Hawk-Bin Kwon; Beom-Gi Kim (Plant Molecular Biology, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

Expression of tobacco tocopherol cyclase in rice regulates antioxidative defense and drought tolerance - Hee-Jong Woo; Soo-In Sohn; Kong-Sik Shin; Jae-Kwang Kim; Beom-Gi Kim; Myung-Ho Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Anoctamin 1 expression in the mouse auditory brainstem - Sang Jae Cho; Ji Hyun Jeon; Do Ill Chun; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2014)

Transcriptome information of the Arctic green sea urchin and its use in environmental monitoring - Jae-Sung Rhee; Bo-Mi Kim; Beom-Soon Choi; Ik-Young Choi; Hyun Park; In-Young Ahn; Jae-Seong Lee (Polar Biology, 2014)

Ectopic expression of CaWRKY1, a pepper transcription factor, enhances drought tolerance in transgenic potato plants - Seok-Jun Moon; Se-Youn Han; Dool-Yi Kim; Beom-Gi Kim; In Sun Yoon; Dongjin Shin; Hawk-Bin Kwon; Myung-Ok Byun (Journal of Plant Biology, 2014)

Effects of strobe light stimulation on postnatal developing rat retina - Jung-a Shin; Eojin Jeong; In-Beom Kim; Hwa-young Lee (Experimental Brain Research, 2014)

Escitalopram block of hERG potassium channels - Yun Ju Chae; Ji Hyun Jeon; Hong Joon Lee; In-Beom Kim; Jin-Sung Choi; Ki-Wug Sung; Sang June Hahn (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Jun Hyung Seo; Hyo Geun Bae; Da Hee Park; Beom Seok Kim; Jong Wook Lee; Jung In Lee; Dong Hyun Kim; Seok Won Lee; Bong Bo Seo (Genes & Genomics, 2013)

A novel COCH mutation associated with autosomal dominant nonsyndromic hearing loss disrupts the structural stability of the vWFA2 domain - Hyun-Ju Cho; Hong-Joon Park; Maria Trexler; Hanka Venselaar; Kyu-Yup Lee; Nahid G. Robertson; Jeong-In Baek; Beom Sik Kang; Cynthia C. Morton; Gert Vriend; László Patthy; Un-Kyung Kim (Journal of Molecular Medicine, 2012)

Developmental expression of plasma glutathione peroxidase during mouse organogenesis - Ki Youn Jung; In-Jeoung Baek; Jung-Min Yon; Se-Ra Lee; Mi-Ra Kim; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2011)

Influence of Short-Term Silicon Application on Endogenous Physiohormonal Levels of Oryza sativa L. Under Wounding Stress - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Hamayun; Sang Mo Kang; Yoon Jung Beom; In-Jung Lee (Biological Trace Element Research, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6 - Jang Hoon Lee; Kyung Cheol Ma; Sug Ju Ko; Beom Ryong Kang; In Seon Kim; Young Cheol Kim (Current Microbiology, 2011)

Synaptic connections of calbindin-immunoreactive cone bipolar cells in the inner plexiform layer of rabbit retina - Shin Ae Kim; Choong Ki Jung; Tae-Hoon Kang; Ji Hyun Jeon; Jiook Cha; In-Beom Kim; Myung-Hoon Chun (Cell and Tissue Research, 2010)

Differential expression of two glutamate transporters, GLAST and GLT-1, in an experimental rat model of glaucoma - Chan Kee Park; Jiook Cha; Soo Chul Park; Phil Young Lee; Jie Hyun Kim; Hwa Sun Kim; Shin Ae Kim; In-Beom Kim; Myung-Hoon Chun (Experimental Brain Research, 2009)

Artificial neural networks for predicting DGPS carrier phase and pseudorange correction - Arif Indriyatmoko; Taesam Kang; Young Jae Lee; Gyu-In Jee; Yong Beom Cho; Jeongrae Kim (GPS Solutions, 2008)

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

Production of Indole-3-Acetic Acid in the Plant-Beneficial Strain Pseudomonas chlororaphis O6 Is Negatively Regulated by the Global Sensor Kinase GacS - Beom Ryong Kang; Kwang Yeol Yang; Baik Ho Cho; Tae Ho Han; In Seon Kim; Myung Chul Lee; Anne J. Anderson; Young Cheol Kim (Current Microbiology, 2006)

Brain-derived neurotrophic factor modulates the dopaminergic network in the rat retina after axotomy - Eun-Jin Lee; Myoung-Chul Song; Hyun-Ju Kim; Eun-Jin Lim; In-Beom Kim; Su-Ja Oh; Jung-IL Moon; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Synaptic connections of cone bipolar cells that express the neurokinin 1 receptor in the rabbit retina - In-Beom Kim; Mi Ra Park; Tae-Hoon Kang; Hyun-Ju Kim; Eun-Jin Lee; Myung-Douk Ahn; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Changes in retinal neuronal populations in the DBA/2J mouse - Jung-Il Moon; In-Beom Kim; Jae-Sung Gwon; Myoung-Hee Park; Tae-Hoon Kang; Eun-Jin Lim; Kyu-Ryong Choi; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Comparative study of cholinergic cells in retinas of various mouse strains - Tae-Hoon Kang; Young-Han Ryu; In-Beom Kim; GooTaeg Oh; Myung-Hoon Chun (Cell and Tissue Research, 2004)

Expression of Interferon Inducible Genes Following Hantaan Virus Infection as a Mechanism of Resistance in A549 Cells - Jae-Hwan Nam; Kyung-A Hwang; Cheong-Hee Yu; Tae-Hoon Kang; Jae-Young Shin; Woo-Young Choi; In-Beom Kim; Young-Ran Joo; Hae-Wol Cho; Keun-Yong Park (Virus Genes, 2003)

Localization of CD15 immunoreactivity in the rat retina - Eun-Jin Lee; Wook-Hyun Shon; In-Beom Kim; Sung-Oh Kwon; Su-Ja Oh; Myung-Hoon Chun (Cell and Tissue Research, 2002)

Reorganization of horizontal cell processes in the developing FVB/N mouse retina - Sung-Jin Park; In-Beom Kim; Kyu-Ryong Choi; Jung-Il Moon; Su-Ja Oh; Jin-Woong Chung; Myung-Hoon Chun (Cell and Tissue Research, 2002)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Morphological analysis of CD15-immunoreactive neurons in the guinea pig retina - In-Beom Kim; Eun-Jin Lee; Jung-Il Moon; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Curdlan gels as protein drug delivery vehicles - Beom Soo Kim; In Duck Jung; Jong Sik Kim; Jung-heon Lee; In Young Lee; Kyung Bok Lee (Biotechnology Letters, 2000)

Double-labeling techniques demonstrate that rod bipolar cells are under GABAergic control in the inner plexiform layer of the rat retina - In-Beom Kim; Mun-Yong Lee; S.-J. Oh; Keun-Young Kim; M.-H. Chun (Cell and Tissue Research, 1998)